Asymmetric causality between exchange rate and interest rate differentials: a test of international capital mobility. (2017) - Dahalan, Jauhari; Mohammed, Umar
The study employs asymmetric causality to reinvestigate international capital mobility. We simulate critical values based on the leverage bootstrapping and asymmetric causality test. The result reveals that positive shocks in exchange rate causes positive shocks in interest rate in Malaysia. This leads to increase capital inflow into Malaysia. The result further indicates that an increase in exchange rate in Malaysia, Nigeria and South Africa during bad time lowers their capital inflow due to low rate of return to the foreign investors. Furthermore, a decrease in the domestic interest rate in Nigeria influences an increase in the exchange rate during the bad time. This causes fall in the demand for domestic currency from foreigners. The policy implication is that Malaysian policymakers can control capital outflow and encourage inflow during both good and bad times. However, the monetary authorities in Nigeria and South Africa can only control the nations' capital mobility during bad time.